The human osteoclast precursor circulates in the monocyte fraction. - Fujikawa, Y; Quinn, J; Sabokbar, A; McGee, J; Athanasou, N (1996)
The osteoclast is known to be formed by fusion of circulating mononuclear precursor cells of haematopoietic origin. The precise nature of these circulating cells and, in particular, their relation to monocytes is unknown. We have developed an in vitro system of human osteoclast formation whereby human monocytes [CD14, CD11a, CD11b and HLA-DR positive, and tartrate-resistant acid phosphatase (TRAP), calcitonin receptor (CTR), vitronectin receptor (VNR) negative] were isolated and cocultured for up to 21 days with UMR106 rat osteoblast-like cells or ST2 mouse preadipocytic bone marrow stromal cells in the presence of 1 alpha, 25 dihydroxyvitamin D3 (1,25(OH)2D3) and macrophage colony stimulating factor (M-CSF). Numerous TRAP, VNR and CTR positive multinucleated cells, capable of extensive lacunar bone resorption, formed in these cocultures; the absolute requirements for this to occur were contact with the above bone stromal cells, 1,25(OH)2D3, and M-CSF. These results show that the human mononuclear osteoclast precursor circulates in the monocyte fraction and exhibits a monocyte phenotype, acquiring osteoclast phenotypic features in the process of differentiation into mature functional osteoclasts.